PEMBINAAN DAN PENGUATAN MANHAJ IDEOLOGI MUHAMMADIYAH GURU DAN PEGAWAI MUHAMMADIYAH BOARDING SCHOOL UNIVERSITAS MUHAMMADIYAH MATARAM - Supratman Supratman,; Isnaini Isnaini,; Humaira Humaira, (JURNAL PENGABDIAN MANDIRI, 2023)
This service is carried out at Muhammadiyah Boarding School, Mataram. It is a new institution at Muhammadiyah University Mataram that requires special guidance and institutional strengthening, especially related to the development and reinforcement of the Muhammadiyah ideology towards teachers and staff. The purpose of this activity is to provide maximum benefit in developing the missionary activities of Muhammadiyah in Amal Usaha Muhammadiyah. The method is held out in several stages: Planning; (1) drafting a proposal for the activity; (2) discussing with partners, namely the Director of MBS UMMAT, to participate in the dedication activity; (3) creating a follow-up plan (RTL); and (4) creating the final dedication report. The results of this service show that the activity helps MBS UMMAT to build the commitment of teachers and staff in understanding the method and ideology as well as the principles of struggle of Muhammadiyah. Thus, the presence of teachers and staff at AUM is not only about working professionally but also carrying the message of missionary activities in accordance with the mission of Muhammadiyah.